(untitled) (Research, Society and Development, 2023)
Objective: Analyze palliative care in Geriatrics, through a systematic review. Methods: A systematic review study, in which the time frame was made over a period of six years (2016 to 2022), in English and Portuguese languages. The following platforms were used as sources of information: MEDLINE/PubMed, LILACS, SCIELO and EMBASE. With the following health descriptors associated with the Boolean operator AND: elderly and palliative care and geriatrics. Results: From the nine articles analyzed for the review, it was possible to verify that the interdisciplinarity aimed at individualized follow-up to the elderly patient and their family, allows better management of physical, psychosocial and spiritual symptoms and a greater understanding of this care, focused on collaborate for holistic patient care, improving care in geriatric palliative care. Non-pharmacological interventions have a relevant role in the action of the geriatrician in palliative care. Conclusion: The field of palliative care is capable of offering a deeply integrated care that can cover up different goals of care in Geriatrics, but that also facilitates a solid shifting process from the goal of functional recovery to goals oriented towards comfort.